Human β-defensin-3 up-regulates cyclooxygenase-2 expression and prostaglandin E2 synthesis in human gingival fibroblasts - P. Chotjumlong (2018)
Chotjumlong P, Khongkhunthian S, Ongchai S, Reutrakul V, Krisanaprakornkit S. Human β-defensin-3 up-regulates cyclooxygenase-2 expression and prostaglandin E2synthesis in human gingival fibroblasts. J Periodont Res 2010; 45: 464-470. © 2010 John Wiley & Sons A/S Background and Objective: Oral epithelial cells express three antimicrobial peptide human β-defensins (hBDs) that have previously been demonstrated to exert proinflammatory effects on various immune cells. We wanted to examine whether hBDs could induce cyclooxygenase-2 (COX-2) expression and prostaglandin E2 (PGE2) synthesis in non-immune cells, such as human gingival fibroblasts. Material and Methods: Cultured fibroblasts were treated with different concentrations of hBD-1, -2, -3 or interleukin-1β, as a positive control, for various times, in the presence or absence of NS-398, a specific COX-2 inhibitor. The levels of COX-1 and COX-2 mRNA expression were analyzed using RT-PCR and real-time PCR. Whole cell lysates were analyzed for COX-1 and COX-2 protein expression by western blotting. Cell-free culture supernatants were assayed for PGE2 levels by ELISA. The lactate dehydrogenase assay was performed to determine the cytotoxicity of hBDs. Results: Ten and 40 μg/mL of hBD-3 up-regulated COX-2 mRNA and protein expression, consistent with COX-2 up-regulation by interleukin-1β, whereas hBD-1 and hBD-2 did not. However, COX-1 mRNA and protein were constitutively expressed. The time-course study revealed that hBD-3 up-regulated COX-2 mRNA and protein expression at 6 and 12 h, respectively. Consistent with COX-2 up-regulation, 10 and 40 μg/mL of hBD-3 significantly increased PGE2 levels in cell-free culture supernatants (p < 0.05), and this was inhibited by NS-398 in a dose-dependent manner. Neither of the hBD concentrations tested in this study was toxic to the cells. Conclusion: These findings indicate that epithelial human β-defensin-3 functions as a proinflammatory mediator in controlling arachidonic acid metabolism in underlying fibroblasts. © 2010 John Wiley & Sons A/S.